THE CULT OF JUPITER AND OF JUNO REGINA IN THE RURAL AREAS OF MOESIA INFERIOR - Lucrețiu Mihailescu-Bîrliba (Journal of Ancient History and Archaeology)
The author analyzes the occurrences of the cult of Jupiter and Juno in the rural milieu of Moesia Inferior. He concludes that most of text which are related to this cult in the whole province come from the rural area. He is connecting the mentionning of this cult with the presence of communities of cives Romani consistentes and the Roman army in the villages of Moesia Inferior.